2018
DOI: 10.1186/s12302-018-0161-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards a holistic and solution-oriented monitoring of chemical status of European water bodies: how to support the EU strategy for a non-toxic environment?

Abstract: The definition of priority substances (PS) according to the Water Framework Directive (WFD) helped to remove many of these chemicals from the market and to reduce their concentrations in the European water bodies. However, it could not prevent that many of these chemicals have been replaced by others with similar risks. Today, monitoring of the PS-based chemical status according to WFD covers only a tiny fraction of toxic risks, extensively ignores mixture effects and lacks incentives and guidance for abatemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 117 publications
0
46
0
Order By: Relevance
“…However, targeted chemical surveillance, as used to assess the chemical status of water bodies in the context of the EU-WFD, only allows to monitor the concentration of priority substances. The presence of unknown chemicals, metabolites, transformation products, or non-regulated substitutes of priority substances are not taken into account [22], but can be considered when using effectbased bioassays [66,68].…”
Section: Bridging the Gap Between Ecological And Chemical Status Withmentioning
confidence: 99%
See 1 more Smart Citation
“…However, targeted chemical surveillance, as used to assess the chemical status of water bodies in the context of the EU-WFD, only allows to monitor the concentration of priority substances. The presence of unknown chemicals, metabolites, transformation products, or non-regulated substitutes of priority substances are not taken into account [22], but can be considered when using effectbased bioassays [66,68].…”
Section: Bridging the Gap Between Ecological And Chemical Status Withmentioning
confidence: 99%
“…In line with this limitation, Carvalho et al [69] have recently shown that EQSs are not sufficiently protective, because they neglect mixture effects of substances, as they occur under field conditions, since EQSs were derived on the basis of single substance tests under controlled laboratory conditions. Therefore, the implementation of effect-based methods in the EU-WFD is gaining importance and is increasingly recommended [22,23,66,67], since effect-based methods integrate biological effects of mixtures of chemicals with the same mode of action [35,68,70,71], as well as antagonistic and synergistic mixture effects [67]. This is one of the main advantages of the present ecotoxicological assessment system.…”
Section: Bridging the Gap Between Ecological And Chemical Status Withmentioning
confidence: 99%
“…Thus, restoration measures on their own will not lead to the desired good ecological status according to EU-WFD unless chemical contamination of water and sediments is reduced in parallel. As our approach provides clear advantages compared to the assessment of the chemical status according to EU-WFD, which focuses only on the concentrations of 45 priority substances and completely neglects effects of metabolites, transformation products, non-regulated substitutes of priority substances and mixture effects of substances [137][138][139][140][141][142][143], while these can be assessed by effect-based in vitro bioassays, we recommend implementing effect-based methods in the EU-WFD [137][138][139]144] and improving water and sediment quality in conjunction with hydromorphological restoration measures to achieve the objectives of the EU-WFD.…”
Section: Comparison Of the Rivers Horloff And Niddamentioning
confidence: 99%
“…In support of this concept, a participatory Ecosystems Services approach for pressure prioritization that enables the integration of Ecosystem Services into River Basin Management Plans would allow a systematic way to prioritize pressures with metrics that directly match with matters that are important for people [33]. -Develop strategies for urban water and pollution management to support smart, sustainable and healthy cities including the assessment of transboundary chemical footprints [34], advancing on the concept of source-related discharge signatures [35] and fingerprints [14]; -Foster science-policy interaction for strengthening policy coherence and harmonized cross-compliance of regulations on chemical, water, energy and environmental conservation and to anticipate upcoming transition pathways, e.g., for implementing a circular and bio-based economy.…”
Section: Recommendationsmentioning
confidence: 99%
“…The scientific and technical means to record unparalleled amounts of data for chemical fingerprinting, toxicological profiles, biological and ecological functions in a yet unachieved resolution are emerging [14,15]. These data offer novel insights to anticipate impacts on biodiversity and ecosystem services as basis for informed decision making.…”
mentioning
confidence: 99%